Family Partnership-Based Environmental Care Learning Model in Creating Child-Friendly Schools in PAUD Melati, Bengkulu City - Dwi Ismawati; Debi S Fuadi; Yenda Puspita; Meli Afrodita; Dwi Lyna Sari; Lenni Mantili Hutauruk (Institut Agama Islam Negeri Madura, 2024)
This research was conducted to see the practicality of an environmental care learning model based on family partnerships in creating child-friendly schools in PAUD Melati, Bengkulu City, which consists of 3 parts, namely: practicality from teachers, parents and observers. This research is a type of research and development (research and development). ). This research procedure refers to the stages of the Borg and development model.This research was conducted at PAUD Melati, Bengkulu City with a total of 62 children, 62 parents and 4 teachers from PAUD Melati, Bengkulu City.Data collection in this research was carried out using observation, interviews and response questionnaire techniques. The results of this research are that the implementation of the model gets a score of 86%, the practicality of the model is seen from its usefulness based on the results of the teacher response questionnaire to the model, the percentage score of teacher 1 is 93%, teacher 2 is 89%, teacher 3 is 91% and teacher 4 is 90% in the very good category and in terms of effectiveness using the anova test, a sig value of 0.00 <0.05 was obtained, which shows that there is a difference after the use of an environmental care learning model based on family partnerships in creating child-friendly schools in PAUD Melati, Bengkulu City